Construction of the Geometrical Models of a Multiple-Factor Optimization of the Technical and Operating Parameters of the Trolleybuses with an Autonomous Move Margin - Serhii Pustiulha; Volodymyr Samchuk; Valerii Dembitskyi; Viktor Samostian; Valentyn Prydiuk (Communications - Scientific letters of the University of Zilina, 2022)
While introducing into a system of passenger traffic the ecologically clean vehicles, namely the electric buses, a task of providing them with a rational move margin is actual. This problem is especially acute while using the trolleybuses with an autonomous move at urban and suburban routes. A constructed multiple-factor model and a proposed algorithm of finding the main parameters allow forming the offers concerning a constructive providing of an additional equipment process with the means of autonomous move. Based on a visual presentation of the multidimensional spaces at Radishchev drawing an effective way is offered of a geometrical interpretation of mutual influence of the optimization factors set on the operating characteristics of the additionally equipped vehicles.